Fractionation of hemicelluloses and lignin from rice straw by combining autohydrolysis and optimised mild organosolv delignification - Moniz, Patricia (2016)
An integrated strategy was followed to valorise rice straw, one of the most relevant biomass feedstocks available worldwide, to selectively recover solubilised hemicelluloses and lignin. The pathway encompassed the use of autohydrolysis to hydrolyse the hemicelluloses and an ethanol-based organosolv process to solubilise lignin. Several autohydrolysis conditions were assayed with the best results obtained at 210 ºC (log R0 4.15), which enabled high removal of hemicelluloses, yielding an oligosaccharide-rich hydrolysate and a treated biomass with low content of hemicelluloses and enriched in cellulose and lignin. The effects of ethanol concentration (5 to 75%), and reaction time (0 to 24 h) on lignin removal under mild temperature (30 ºC) were studied. In optimal conditions (60.5% ethanol, 24h) the delignification yield reached 42%, where as glucan solubilisation was below 17%. Lignin solubilisation yield was not influenced by the organosolv treatment duration while ethanol concentration favored the delignification up to 60.5% ethanol. The organosolv liquors contained economic interesting ligninderived compounds such as vanillin, ferulic, and coumaric acids. The chemical composition and enzymatic digestibility of the treated biomass from autohydrolysis and organosolv delignification were compared, with the latter presenting an almost 10% higher enzymatic digestibility than the former.